2022
DOI: 10.1038/s41419-022-05152-6
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a BRAF/PA28γ/MEK1 signaling axis and its role in epithelial-mesenchymal transition in oral submucous fibrosis

Abstract: Oral submucous fibrosis (OSF) is a chronic and insidious oral potentially malignant disorder associated with a 4–17% risk of oral squamous cell carcinoma (OSCC). Our previous study found that proteasomal activator 28 gamma (PA28γ) is frequently overexpressed in oral squamous cell carcinoma and negatively correlated with poor patient prognosis. However, the role of PA28γ in the occurrence and development of OSF remains unclear. Here, we screened PA28γ-related genes and investigated their function in OSF. We dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…32 Our previous study found that arecoline can activate the BRAF/MEK1 signaling pathway in epithelial cells, which ultimately promotes epithelialmesenchymal transition. 33 However, it is not clear how epithelial cells drive the differentiation of broblasts to participate in brosis development.…”
Section: Discussionmentioning
confidence: 99%
“…32 Our previous study found that arecoline can activate the BRAF/MEK1 signaling pathway in epithelial cells, which ultimately promotes epithelialmesenchymal transition. 33 However, it is not clear how epithelial cells drive the differentiation of broblasts to participate in brosis development.…”
Section: Discussionmentioning
confidence: 99%
“…The primary psychoactive component of areca nuts, arecoline (Are), has been identified as a Group I human carcinogen by the International Agency for Cancer Research, 15,16 and has been shown to significantly increase the risk of oral and ECs 17,18 . Chewing areca nuts can result in the mouth conditions of oral submucous fibrosis (OSF) and oral squamous cell carcinoma (OSCC), both of which have the potential to develop into cancer 19,20 . In OSCC and OSF, 18 arecoline has the ability to cause inflammation and release reactive oxygen species (ROS) 17 .…”
Section: Introductionmentioning
confidence: 99%
“…17,18 Chewing areca nuts can result in the mouth conditions of oral submucous fibrosis (OSF) and oral squamous cell carcinoma (OSCC), both of which have the potential to develop into cancer. 19,20 In OSCC and OSF, 18 arecoline has the ability to cause inflammation and release reactive oxygen species (ROS). 17 Arecoline's effects on esophageal epithelial cells have not been thoroughly understood, though.…”
mentioning
confidence: 99%
“…Lesions of LP in the oral mucosa can hinder the patient’s ability to eat, while those on exposed skin can significantly disrupt their social and daily activities. Oral lichen planus, a potentially malignant disorder, has no known cure and carries the risk of progressing into oral squamous cell carcinoma ( 12 , 13 ). Thus, early detection and appropriate management of oral lichen planus are crucial in preventing the development of oral cancer.…”
Section: Introductionmentioning
confidence: 99%